DBT System in MGNREGA: An Analysis of its Role in Reducing Corruption and Enhancing Transparency in Dhanbad District, Jharkhand - Sudhanshu Priyadarshi1, Dr. K.K. Pathak2 (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2024)
A flagship initiative of the Indian government aiming at improving livelihood security in rural areas is the Mahatma Gandhi National Rural Employment Guarantee Act (MGNREGA). Still, its execution has been tarnished by lack of openness and corruption. In the framework of the Dhanbad District, Jharkhand, this paper examines the efficiency of the Direct Benefit Transfer (DBT) system in handling these problems. This study looks at how DBT might lower corruption, increase transparency, and improve general program efficiency using a mixed-methods approach comprising surveys, interviews, and analysis of government data. The results imply that even although DBT has greatly lowered some forms of corruption and enhanced openness, technology infrastructure, financial inclusion, and local government still present issues. The study offers suggestions for legislators and executioners to enhance the DBT system in MGNREGA even more.